ANALYZING EFFECTIVENESS OF TEACHING ENGLISH VOCABULARY WITH MODERN INFORMATION AND COMMUNICATION TECHNOLOGIES TO YOUNG LEARNERS. (Journal of Universal Science Research, 2025)
This study reviews the effectiveness, challenges and solutions of teaching vocabulary to young learners with the help of modern information and communication technologies.